mRNA Stability and Polysome Loss in Hibernating Arctic Ground Squirrels (Spermophilus parryii) - Knight, Jason E. (American Society for Microbiology, 2000)
All small mammalian hibernators periodically rewarm from torpor to high, euthermic body temperatures for brief intervals throughout the hibernating season. The functional significance of these arousal episodes is unknown, but one suggestion is that rewarming may be related to replacement of gene products lost during torpor due to degradation of mRNA. To assess the stability of mRNA as a function of the hibernation state, we examined the poly(A) tail lengths of liver mRNA from arctic ground squirrels sacrificed during four hibernation states (early and late during a torpor bout and early and late following arousal from torpor) and from active ground squirrels sacrificed in the summer. Poly(A) tail lengths were not altered during torpor, suggesting either that mRNA is stabilized or that transcription continues during torpor. In mRNA isolated from torpid ground squirrels, we observed a pattern of 12 poly(A) residues at greater densities approximately every 27 nucleotides along the poly(A) tail, which is a pattern consistent with binding of poly(A)-binding protein. The intensity of this pattern was significantly reduced following arousal from torpor and undetectable in mRNA obtained from summer ground squirrels. Analyses of polysome profiles revealed a significant reduction in polyribosomes in torpid animals, indicating that translation is depressed during torpor.